(3TQM Yjhf GdMceIs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s ((3jhSa Hf EHQGgje Hf CHj GdcQe GdJcQjJj s)
(3ChdgG (B:s
(3CeG HYO aEf cJGH Yjhf GdMceeI cJGH CNHGQg SWQJ ai UaGFM GdeaGNQ bGd GdTjN gPG cJGH eTJed Ydi KdGKI CbSGe efWb hWHjYi hEdgi GdJYHjQ ggfG eSGFd GdeSFdI GdChdi ai HjGf Cf GdefWb s
(3BNQgG (B:s
(3hGdEfbWGY eTGgOg YbdjI hgPg cdeGJ TQjaI heYGfjgG WGgQI hdGJLYdfi ef GdgGdcjf jG CcQe GdCcQejf hjG CQMe GdQGMejf hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs